Ultrastructural and morphometric analysis of enlarged platelets in congenital isolated asplenia - Markovic, Olivera; Martinovic, Tamara; Ciric, Darko; Trpinac, Dusan; Cemerikic-Martinovic, Vesna; Bumbaširević, Vladimir; Bila, Jelena; Marisavljević, Dragomir; Kravic-Stevovic, Tamara (Vojnosanitetski pregled, 2021)
Abstract Introduction. Congenital asplenia is an extremely rare condition that can be separate entity due to a specific defect of spleen development or may occur in the context of a malformation syndrome. The patients with asplenia have thrombocytosis and susceptibility to life-threatening infections. Case report. We report a 52-years-old female patient with isolated congenital asplenia with pseudothrombocytopenia and giant platelets. Estimation of platelets life with radioactive indium showed normal lenght of platelets life (9 days). Flow cytometric analysis of platelets showed normal expression of CD41 and CD42b antigens. The mean platelet diameter of asplenic patient measured on the ultrathin sections by the transmission electron microscope was significantly higher than in the healthy individuals (3.81 ± 1.16 µm vs. 2.37 ± 0.61 µm, p < 0.05). There were very few platelets of diameter more than 4 μm found in healthy individuals (around 1%) in comparison to > 40% of the patient’s platelets. The ultrastructural studies revealed normal morphology of megakaryocytes. The platelets were uniformly spheroid in shape with conspicuous pseudopodia and the centralization of granules. There were no marginal bands of microtubules inside the platelets. Conclusion. The first case of congenital asplenia with the pseudothrombocytopenia and giant platelets is presented. We discussed the pathogenesis of giant platelets and possible relation of observed ultrastructural changes of platelets with the severe three-vessel coronary artery disease in our patient.